Verification of automated latex-enhanced particle immunoturbidimetric D-dimer assays on different analytical platforms and comparability of test results - Lapić, Ivana; Coen Herak, Désirée; Prpić, Snježana, biokemičarka; Prce, Andrea; Raščanec, Vanja; Zadro, Renata; Rogić, Dunja, biokemičarka (2020)
Introduction: The aim of the study was the analytical verification of automated latex-enhanced particle immunoturbidimetric (LPIA) D-Dimerassay INNOVANCE D-dimer on Sysmex CS-5100 and Atellica COAG 360 analysers, and HemosIL D-dimer HS500 on ACL TOP 550, as well as the comparisonwith the enzyme-linked immunofluorescent assay (ELFA) on the miniVidas analyser.Materials and methods: Verification included assessment of within-run and between-run precision, bias, measurement uncertainty (MU), verificationof the cut-off, method comparison between all assessed assays, and the reference commercial ELFA VIDAS D-Dimer Exclusion II.Results: Within-run coefficients of variations (CVs) ranged from 1.6% (Atellica COAG 360) to 7.9% (ACL TOP 550), while between-run CVs rangedfrom 1.7% (Sysmex CS-5100) to 6.9% (Atellica COAG 360). Spearman’s rank correlation coefficients were >0.99 between LPIAs and ≥ 0.93 whencomparing ELFA with LPIA. Passing-Bablok regression analysis yielded constant and proportional difference for comparison of ACL TOP 550 withboth Sysmex CS-5100 and Atellica COAG360, and for miniVidas with Atellica COAG360. Small proportional difference was found between miniVidasand both Sysmex CS-5100 and ACL TOP 550. Calculated MUs using D-dimer HS 500 calibrator were 12.6% (Sysmex CS-5100) and 15.6% (Atellica COAG360), while with INNOVANCE D-dimer calibrator 12.0% (Sysmex CS-5100), 10.0% (Atellica COAG 360) and 28.1% (ACL TOP 550). Excellent agreementof results was obtained, with occasional discrepancies near the cut-off. The cut-off (0.5 mg/L FEU) was confirmed.Conclusions: The obtained results prove satisfactory analytical performance of LPIAs, their high comparability and almost equal discriminatorycharacteristics, suggesting them as a valid alternative to ELFA.
Bibliografija: 29 jed.
Summary.
Keywords: Hemostaza -- Zgrušavanje krvi -- D-dimer -- Imunoturbidimetrija -- Validacijska analiza